STIGMA TERHADAP PENDERITA SKIZOFRENIA DALAM MANGA BURAKKU JAKKU NI YOROSHIKU KARYA SHUHO SATO - Komalasari, Priti (Humanis, 2015)
This study entitled “Stigma Against Schizophrenic People in Burakku Jakku ni Yoroshiku Comics by Shuho Sato”, is analyzed using the theory of literature sociology and supported by social stigma and semiotic. Based on the analysis that has been done, schizophrenic people have experienced three types of stigma, such as to be considered a dangerous people, weak people, and bad people. The impact of those stigma are discrimination from family, discrimination from society, discrimination in medical services and discrimination in workplace. The effort to reduce stigma toward schizophrenic people are done by Japanese government, society who care with schizophrenic people, and schizophrenic people themselves.
Keywords: Schizophrenia, stigma, impact